Self-appreciation is not enough: exercise identity mediates body appreciation and physical activity and the role of perceived stress - Shi, Linyu; Jiang, Lixia; Zhou, Song; Zhou, Wenbo; Yang, Huaqi (Frontiers in Psychology, 2024)
People who respect their body image are thought to engage in physical activity proactively; however, whether this positive attitude towards body image is bound to promote exercise remains unclear. This study aims to investigate the relationship between body appreciation and physical activity from the perspective of exercise identity. We conducted a short-term longitudinal survey, recruiting 345 college students (100 females, 245 males; 𝑀 𝑎𝑔𝑒 = 22.94, SD = 5.99) who completed questionnaires at two-week intervals for a total of three times within four weeks. Body appreciation, exercise identity, perceived stress, and physical activity were measured for the participants separately. The results demonstrated that body appreciation positively predicted physical activity, exercise identity partially mediated the positive effect of body appreciation on physical activity, and perceived stress played a moderating role in body appreciation and exercise identity. These findings shed light on the behavioral impact of body appreciation, and the correlation between body appreciation and physical activity was stronger when levels of perceived stress levels were lower.